Seasonal dynamics and spatial distribution of lepidopterans in selected locations in Mordovia, Russia - ALEXANDER B. RUCHIN (Society for Indonesian Biodiversity, 2021)
Abstract. Ruchin AB. 2021. Seasonal dynamics and spatial distribution of lepidopterans in selected locations in Mordovia, Russia. Biodiversitas 22: 2569-2575. The research was conducted in 2019-2020 in the Republic of Mordovia (European part of Russia). In order to collect Lepidoptera, beer traps were used where beer served as bait. The field surveys were carried out from April to October in various forest habitats. The air temperature was recorded. To elucidate the spatial distribution of Lepidoptera, various habitats were examined in two study plots. In total, more than 23 thousand Lepidoptera specimens were examined. The largest number of Lepidoptera was collected in oak forests in contrast to the four other forest habitats. In all habitats, population dynamics were similar and characterized by the same trends of decrease and increase. During the season, there were three peaks of abundance for this group. A moderate first peak was recorded in the second half of May, while the maximum peak occurred in the first half of July. Autumn population peaks depend on temperature, while spring and summer peaks are associated with the flight of imagos and an increase in the lepidopteran abundance in habitats. In open habitats, the abundance of Lepidoptera was lower. On forest edges, the number of Lepidoptera considerably exceeded one in open habitats (river sandbanks, willow thickets, forest glades, and floodplain meadows) and closed habitats (inside the forests). Forest edges are a hotspot of Lepidoptera abundance and biodiversity in forest habitats. According to the vertical gradient, the number of lepidopterans was higher at the height of 7.5 m than at the height of 1.5 m. At the lower height, the number of Lepidoptera did not vary as considerably as at higher heights